ANALISIS SISTEM PELUMASAN PADA MESIN HOBBING - Giovani Sendi Agustian Louhenapessy (2021)
Lubrication viscosity and temperature have a very strong bond and role in the process of energy loss in the form of heat. Temperature prediction on gearbox components is divided into four basic elements, namely optimization, analysis of possibilities or alternatives, heat reduction without lubricant, and possibilities that can occur in the future. the effect of providing lubrication on hobbing machine. The method of data collection in writing this thesis is to use the literature study method, using reference books that can add insight to the theory related to Hobbing and Lubrication Machines, providing guidance with supervisors in the field and supervisors in lectures; and by browsing the Internet, by using articles related to theses. Based on the results of the analysis and discussion above, the conclusions in this study include: Damage to the hobbing machine process is caused by excessive friction in the transmission with an indication that there is no change in transmission lubricant according to the reference period of use. Solid lubricants have a very good load-bearing ability and a fairly good 700-3000 rpm rotational capability, but both properties are temporary. semi solid lubricant, the ability to withstand loads is very good, the ability at 700-3000 rpm is not good and there is no liquid lubricant filtering process, the load-bearing ability is quite good and the ability at 700-3000 rpm is very good. This is because liquid lubricants can coat parts that cannot be reached by other types of lubricants because of their low viscosity